A Transdisciplinary Approach to Equitable Teaching in Early Childhood Education. Issue 1 (March 2019) - Souto-Manning, Mariana; Falk, Beverly; López, Dina; Barros Cruz, Lívia; Bradt, Nancy; Cardwell, Nancy; McGowan, Nicole; Perez, Aura; Rabadi-Raol, Ayesha; Rollins, Elizabeth
In this review of research, we offer a meta-analysis of young children's learning and development within and across psychology, education, and linguistics. Engaging with Soja's concept of Thirdspace, we mapped young children's learning and development transdisciplinarily, seeking to (re)conceptualize early childhood teaching in ways that are answerable to intersectionally minoritized children, families, and communities of color—those whose voices, values, perspectives, and knowledges have been historically and continue to be contemporarily marginalized. To do so, we identified seven principles with the potential to transform early childhood teaching practice. We posit that together these principles can shift the architecture of early childhood teaching, offering promising possibilities for fostering equity by allowing us to move toward emancipatory praxis and negotiate practical solutions to education's long history of inequities and oppressions.